Generalized deformed SU(2) algebras in Nuclear Physics - Bonatsos, Dennis; Daskaloyannis, C.; Kolokotronis, P. (HNPS Advances in Nuclear Physics, 2020)
A generalized deformed algebra SUφ(2), characterized by a structure function Φ. is obtained. The usual SU(2) and SUq(2) algebras correspond to specific choices of the structure function Φ. The action of the generators of the algebra on the relevant basis vectors, as well as the eigenvalues of the Casimir operator, are easily obtained. Possible applications in improving phenomenological nuclear models are discussed.